2020
DOI: 10.3390/vetsci7030117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Serological Footprints of Mycobacterium avium Subspecies Infections in Zoo Animals

Abstract: Background: Mycobacteria of the Mycobacterium avium complex (MAC) pose a significant risk to zoological collections. Mycobacterium avium subspecies paratuberculosis (MAP) is a member of MAC and the causative agent of Johne’s disease. Despite many reports in animals kept in zoological gardens, systemic surveillance has rarely been reported. Methods: In this study, archived serum samples collected from animal species at the Wilhelma Zoological and Botanical Gardens in Stuttgart, Germany, were screened for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…In the case of MAC, the ability of the microorganisms to persist in the environment for many years, especially in soil contributes to the disease transmission. However, the prevalence of avian mycobacteriosis in zoo collections is usually low, but each individual case may have devastating consequences for sanitary status of the population so quarantine and surveillance for other infected birds are usually considered good practices in these cases (17,24).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of MAC, the ability of the microorganisms to persist in the environment for many years, especially in soil contributes to the disease transmission. However, the prevalence of avian mycobacteriosis in zoo collections is usually low, but each individual case may have devastating consequences for sanitary status of the population so quarantine and surveillance for other infected birds are usually considered good practices in these cases (17,24).…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of MAC members from the blood showed how ubiquitous these environmental bacteria could be. Many studies showed that M. avium positive samples by PCR were detected from tissues of macaques [ 9 , 10 , 58 , 59 ]. For this reason, epidemiological studies about MAC are important for public health concerns [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis (MAP) [ 9 ]. Members of MAC are not species-specific and are frequently associated with animal or human diseases that resemble tuberculous-like lesions in lymph nodes and parenchymatous organs [ 10 ]. Various outbreaks of MAC infection have been reported in humans and NHP worldwide [ 9 , 10 , 11 ]; however, the relevance of free-ranging NHP for MAC transmission among animals and to humans is unclear [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly affected species are ruminants; however, other mammals are also susceptible [ 2 , 3 ]. In zoos, paratuberculosis has been confirmed among Bovidae [ 4 , 5 , 6 ], Cervidae [ 7 ] Giraffidae [ 8 , 9 ], Camelidae [ 10 , 11 ], Rhinocerotidae [ 12 , 13 ], and Rodentia [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%